Effect of the Nursing Program for Phototherapy-Treated Jaundiced Infants on the Phototherapy Treatment Duration and the Events of Disagreeing to Be Treated with Phototherapy Treatment, Postpartum Ward at Phra Nakhon Si Ayutthaya Hospital - พงศ์ภัทรพร รมณ (Journal of Preventive Medicine Association of Thailand, 2018)
This research is a Quasi Experimental Study, two-group posttest-only design. Its objective is the duration of the phototherapy treatment and the cases of patients disagreeing to be treated with phototherapy, including those under the nursing program as well as those treated normally, were compared. The sampling population included the mothers whose jaundiced infants were treated by phototherapy and their infants. The sampling population, moreover, was chosen by Purposive Sampling Technique. The sampling population was divided into 60 pairs, 30 were treated under the nursing program whereas the other 30 were treated normally. The research instruments applied included the nursing program for jaundiced infants, the survey evaluating the knowledge of caring for phototherapy-treated jaundiced infants and the forms used to record phototherapy treatment duration as well as the events of disagreeing to be treated with phototherapy treatment. In addition, the survey evaluating the knowledge of caring for phototherapy-treated jaundiced infants was sent to evaluate its Reliability Value, which was found out to be .91. The data were collected between October, 2016 and March, 2017. Then, the data were analyzed by comparing different durations of phototherapy treatment by using the statistics of Independent t-test. After experimenting, it was found out that the phototherapy treatment duration of the infants under the nursing program for the phototherapy-treated jaundiced infant ( =2.53, S.D=.629) was less than the ones treated normally (=3.07, S.D=.521) significantly at p=.001. Furthermore, the events of disagreeing to be treated with phototherapy treatment decreased. Three cases of the group treated normally disagreed to be treated with phototherapy treatment. Whereas none of the group of the jaundiced infants under the nursing program disagreed to be treated with phototherapy treatment. The nursing program for phototherapy-treated jaundiced infants was absolutely essential. The processes required include sorting out the risky groups of infants, evaluating the jaundice condition, informing necessary information concerning jaundice to the infants’ mothers, and educating the mothers in the proper way of treating jaundiced infants under the phototherapy treatment. These processes would help the infants to get prompt and effective phototherapy treatment as their mothers and families understand and cooperate in phototherapy treatment.